SOURCES OF A TRANSLATOR'S KNOWLEDGE IN TRANSLATION OF A GERMAN JUDGEMENT AND CORRECTNESS OF THE TRANSLATION - SEKUŁA, Justyna (Comparative Legilinguistics, 2018)
This article discusses the advantages and disadvantages of the use of selected sources of the knowledge of translator (dictionaries, parallel texts and online resources) in translation, the results of the experiments in the scope of specialized translation teaching and the practical implications resulting for carrying out classes of specialist translations and educating translators of the ability to make effective use of the available sources of knowledge when trans-lating legal texts ‒ court judgments.